Radiofrequency catheter ablation increases mean platelet volume - Aksoy,Fatih (2019)
SUMMARY OBJECTIVE Radiofrequency ablation (RFA) may increase the risk of thromboembolic events. The objective of this study was to evaluate the effect of RFA on mean platelet volume (MPV), an indicator of platelet activity. METHODS A total of 95 patients undergoing RFA were included in the study. MPV was measured before and one month after the procedure. The control group was formed by 83 individuals of the same sex and age as those in the study group. RESULTS Beta-blockers, non-dihydropyridine calcium channel blockers, and acetylsalicylic acid use was higher in the ablation group compared with the control group. Other baseline clinical characteristics and baseline hemoglobin, white blood cell count, platelet count, and MPV values were similar between the ablation and control groups. In the ablation group, baseline and post-procedural hemoglobin, white blood cell counts were similar. However, postprocedural MPV values were higher, and platelet counts were lower compared with the preprocedural values. CONCLUSION Our results indicate that MPV values are higher after RFA compared with baseline values.